Ukrainian Scientific and Technical Terminology Formation and Development Peculiarities - Doroshenko, Svitlana; Lysenko, Alla; Tievikova, Olga (International Journal of Engineering and Technology, 2018)
Terminological vocabulary of Ukrainian language has ancient history which starts since the tenth century. The first attempts to collect and arrange Ukrainian scientific and technical terminology started since the second half of the nineteenth century. Lviv scientific community by T. H. Shevchenko leads terminology work systematically since the nineties. The aim of the community was to create science in Ukrainian language which foresaw formation of national scientific terminology. Ukrainian scientific and technical terminology developed most intensively in the twenties of the twentieth century. Creation of the Institute of Ukrainian Scientific Language contributed to this process. Its scientists compiled and published more than forty terminological dictionaries in different branches of science and technique. The main task and research topic of Ukrainian terminologists during the thirties-eighties in the twentieth century was ultimate approaching of Ukrainian and other national terminologies to Russian one. In the article the authors pay attention to the fact that nowadays not all branches of science and technique have perfect Ukrainian terminology. Creation and unification of necessary terminology is a primary task for terminologists.Â Â